A Study on the Construction of an Evaluation Index System for the Educational Effect of College Volleyball Courses from the Perspective of Cultivating the Spirit of Putting the Motherland First - Lin, Li; Lin, Changdi; Shi, Yubin (Education Insights, 2026)
Cultivating virtue and educating people remains the fundamental task of higher education in the new era, and the patriotic spirit of "putting the motherland first" serves as the core soul and value foundation of this comprehensive cultivation process. Integrating this profound spirit organically into college volleyball courses represents an essential task for modern college physical education to successfully implement the broader strategy of moral and academic development. However, a comprehensive review of current electronic literature reveals that researchers have not yet identified or established a standardized evaluation index system for assessing the effectiveness of college volleyball courses in cultivating this patriotic spirit. This critical gap makes it exceedingly difficult to accurately diagnose, monitor, and continuously improve the overall effectiveness of moral education within this specific athletic context. Therefore, this study addresses this significant academic void by utilizing a robust methodological framework that includes the literature research method, the Delphi method, the analytic hierarchy process (AHP), and rigorous mathematical statistics. Taking the cultivation of the spirit of "putting the motherland first" as a primary starting point, this research aims to systematically construct a comprehensive evaluation index system for the educational effectiveness of college volleyball courses. Ultimately, this newly developed framework provides a reliable scientific basis for the quantitative evaluation of patriotic education in collegiate sports. Furthermore, it offers substantial practical support for the successful implementation of the fundamental task of cultivating virtue and educating people across diverse physical education curricula.